Current strategies of virotherapy in clinical trials for cancer treatment. Issue 8 (23rd April 2021) - Lin, Weijian; Zhao, Yongxiang; Zhong, Liping
Abstract: As a novel immune‐active agent for cancer treatment, viruses have the ability of infecting and replicating in tumor cells. The safety and efficacy of viruses has been tested and confirmed in preclinical and clinical trials. In the last decade, virotherapy has been adopted as a monotherapy or combined therapy with immunotherapy, chemotherapy, or radiotherapy, showing promising outcomes against cancer. In this review, the current strategies of viruses used in clinical trials are classified and described. Besides this, the challenge and future prospects of virotherapy in the management for cancer patients are discussed in this review.